The Personality of a Teacher in the Good Doing of Academician Ivan Zyazyun (to the 80th Birthday Anniversary) - Hryhoriy Vasianovych (Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the works by academician Ivan Zyazyun in the framework of the teacher's good doing. It is proved that the prominent scientist of Ukraine considered this problem on the humanistic principles of human creation and the existential nature of human existence. I. Zyazyun states that human is the only living being that does not belong to its lineage group from the moment of birth. Its human essence is acquired throughout whole life. I. Zyazyun as the philosopher and the teacher substantiated the opinion, according to which the worldview of a personality becomes determinant in the process of good going. The humanistic worldview of the personality of a teacher allows creating of his/her own activity aimed at mental, spiritual and intellectual development of students, and to treat them as active and equal subjects of the educational process. Good doing of a teacher forms the spiritual elite of the nation. The spiritual elite is distinguished by the fact that it forms the ideals of good, unites the best forces of the nation to make new cultural achievements. The scholar paid considerable attention to the issues of forming common and collective good doing. It allows all the members of the team to act responsibly, actively and productively for the approval of not only individual but also the common good and welfare.